Classification and monitoring of changes in land cover and land use in the specified area between The Tigris and Al-Azim rivers and the Hamrin range of hills, using remote sensing techniques - qawwam, Quds oawam (Al-Adab Journal, 2015)
Land survey and classification of its uses are among the most prominent applied fields in Geomorphology. The process basically depends on analyzing and classifying land shape. Remote sensation and geographical data systems are among modern means of land use survey and classification, as they facilitate implementation of projects with high speed, accuracy and low cost as well as high flexibility in monitoring changing of land use, in comparison with traditional technologies. Detection data on July 6th 1976 and September 19th 2007 by the American Satellites Mss 7, Land Sat, Land Sat2, and ETM are used and they were processed to enable uncovering land units, land cover and land use. The percentages of land cover and land varied, as increase or decrease can be found among categories. The percentage of arable land category has increased from 6.5242% to 25.1493% out of the total area of study; an average of change mounts to 285.111% between 1976 and 2007. Whereas area allocated as water resources land decreased from 0.6033% of the total area of study in 1976 to 0.4215% in 2007 for a negative change amounts to -30.1884%. Barren land, which forms 92.8725% in 1976, decreased to 69.2458% of the total area of study in 2007, a negative change of -25.1776% between 1976 and 2007. Other categories witnessed increase in change percentages.Key words: Remote sensation, land cover, Adhaim River, the Tigris, Hemrin